Enhancing Napier grass growth under greenhouse conditions using Bacillus and Trichoderma bioproducts - Faydach, Kamonphan; Leesutthiphonchai, Wiphawee; Kasem, Supot; Umrung, Sarinna; Banjerdkij, Peerakarn; Panyasak, Arthit; Tawornpruek, Saowanuch; Khewkhom, Netnapis (Agriculture and Natural Resources, 2026)
Importance of the Work: Sustainable forage production was enhanced by addressing the limited data on microbial bioproduct effects in Napier grass cultivation. Objectives: To evaluate the effects of Bacillus and Trichoderma bioproducts on Napier grass growth, nutrient uptake and physiological responses. Materials and Methods: Two Napier grass cultivars were treated under greenhouse conditions with powdered Bacillus or liquid T. asperellum formulations. Growth parameters, nutrient content, chlorophyll, enzyme activities and indole-3-acetic acid (IAA) content were measured. Treatments were applied at varying frequencies and concentrations, with statistical analyses performed based on analysis of variance and t tests. Results: The microbial bioproducts significantly (p < 0.05) enhanced the growth and physiological performance of Napier grass under greenhouse conditions. Bacillus and Trichoderma increased plant height and leaf number, with responses varying by cultivar and plant age. Bacillus improved the chlorophyll content, particularly in Pak Chong 1, while Trichoderma consistently promoted leaf development. Fresh biomass gains were significant only in the Taiwan treated with Bacillus. The enzyme activity analysis confirmed that Trichoderma stimulated β-1,3-glucanase and peroxidase, whereas Bacillus elevated IAA, indicating distinct microbial effects on plant physiology. Main Finding: Microbial bioproducts, particularly Bacillus and T. asperellum, improved the growth and physiology of Napier grass in a cultivar-specific manner, with Bacillus enhancing the chlorophyll and IAA contents and Trichoderma stimulating β-1,3-glucanase and peroxidase activities.